2020
DOI: 10.5433/1679-0359.2020v41n3p995
|View full text |Cite
|
Sign up to set email alerts
|

Structure of piatã palisadegrass deferred for two periods and fertilised with nitrogen

Abstract: The deferred pasture structure determines the consumption and performance of grazing animals and, in addition, can be influenced by the duration of the deferment period and nitrogen (N) fertilisation. The objective of this work was to evaluate the structural characteristics of Brachiaria brizantha syn. Urochloa brizantha cv. Piatã (piatã palisadegrass) deferred for two periods (79 and 127 days) and with four N doses (0, 40, 80 and 120 kg ha-1) in the Zona da Mata of Minas Gerais, Brazil. The experimental desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…For these purposes, N rates varying from 40 up to 90 kg N ha −1 are normally suggested [87,88] for most Urochloa species. In [81], the authors showed that in pastures subjected to stockpiling in late summer, aimed at grazing during the dry season (winter), a N rate equivalent to 50 kg N ha −1 would be enough to sustain pasture growth potential when N is regularly applied during the previous active growth period.…”
Section: Moving To a New Approach On N Fertilization For Tropical Per...mentioning
confidence: 99%
“…For these purposes, N rates varying from 40 up to 90 kg N ha −1 are normally suggested [87,88] for most Urochloa species. In [81], the authors showed that in pastures subjected to stockpiling in late summer, aimed at grazing during the dry season (winter), a N rate equivalent to 50 kg N ha −1 would be enough to sustain pasture growth potential when N is regularly applied during the previous active growth period.…”
Section: Moving To a New Approach On N Fertilization For Tropical Per...mentioning
confidence: 99%
“…Santos et al (7) argued that the fallowing leads to the accumulation of mature stems and dead material and a decrease in the availability of leaves, with a consequent reduction in animal consumption and performance. Pastures managed at different heights provide different forage masses, interfering with the availability and accessibility of pastures to animals, affecting intake by grazing animals and the animal (30,31) . On the other hand, the botanical composition of the diet for goats, sheep and cattle in the caatinga tends to adjust to the frequency, availability and supply of dry matter (35) , with emphasis on species with better nutritional value (36,37) , especially in protein (38) .…”
Section: Resultsmentioning
confidence: 99%
“…Of the U. brizantha cultivars, research work on stockpiling pasture has been carried out predominantly with the Marandu and Piatã cultivars. For these grasses, there are scientific studies that allow understanding the effects of stockpiling period (Gouveia et al, 2017;Rocha et al, 2020), canopy height before stockpiling (Sousa et al, 2013;Nogueira et al, 2020), and nitrogen fertilization on stockpiled canopies (Alves et al, 2019;Sousa et al, 2019). However, for the Xaraés and Paiaguás cultivars, there is still no available scientific information to guide the management of these grasses under stockpiling.…”
Section: Introductionmentioning
confidence: 99%